Attitudes of Teachers towards Teaching Profession Trained through Formal and Distance Mode - Jain, Rachna (JOURNAL OF INDIAN EDUCATION, 2012)
This study was undertaken with the objective to compare the attitudes of teachers towards teaching profession who have been trained through formal and distance mode with respect to type of school and teaching experience. A standardised attitude scale developed by Goyal (1984) is used profitably for measuring attitude of teachers towards teaching. The scale consists of 22 items. Ten items are favourable, ten items are unfavourable and the remaining two are neutral towards teaching. The scale was administered to 75 teachers trained through distance mode teaching in secondary classes of Delhi schools to collect the data. There was significant difference in the attitude towards teaching profession, of government and private school teachers. The private school teachers have more favourable attitude towards teaching profession as compared to government school teachers. Though both the groups were trained through distance mode, less experienced teachers have more favourable attitude towards teaching profession as compared to more experienced teachers.